2005
DOI: 10.1097/01.tp.0000161667.99145.20
|View full text |Cite
|
Sign up to set email alerts
|

Low Incidence of Acute Rejection after Living-Donor Liver Transplantation: Immunologic Analyses by Mixed Lymphocyte Reaction using a Carboxyfluorescein Diacetate Succinimidyl Ester Labeling Technique

Abstract: The results of CFSE-MLR assays, which could be used for rigorously monitoring rejection, provided evidence of low incidence of acute rejection after LDLT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 24 publications
1
56
0
1
Order By: Relevance
“…T-cell proliferation was visualized by twofold serial dilutions of the fluorescence intensity of CFSE. CD4 + and CD8 + T-cell proliferation and stimulation index (SI) were quantified using a previously described method [15,16].…”
Section: Immune Monitoring By In Vitro Mlr Assaysmentioning
confidence: 99%
“…T-cell proliferation was visualized by twofold serial dilutions of the fluorescence intensity of CFSE. CD4 + and CD8 + T-cell proliferation and stimulation index (SI) were quantified using a previously described method [15,16].…”
Section: Immune Monitoring By In Vitro Mlr Assaysmentioning
confidence: 99%
“…Methyl prednisolone (1 g/day) was intravenously administered for 3 consecutive days (one or two courses) to treat histologically proven or mixed lymphocytic reactionproven acute cellular rejection (37).…”
Section: Immunosuppressionmentioning
confidence: 99%
“…CFSE labeling to assess alloantigen responses has been used widely in murine systems (52). CFSE-MLR assay was used recently in a single human study of living-donor liver transplant recipients to distinguish rejection on suspicious biopsies (53). Despite the theoretic appeal of this assay, to date, no human studies have demonstrated a correlation between donor antigen-induced proliferation and the ability to wean immunosuppression or the development of tolerance.…”
Section: Measurement Of Cell Proliferation By Cfse Labelingmentioning
confidence: 99%